KREATIVITAS SENI BATIK DI DESA WISATA JARUM KECAMATAN BAYAT KLATEN JAWA TENGAH PADA MASA PANDEMI COVID-19 - Sugeng Wardoyo; Tri Wulandari (Institut Seni Indonesia Yogyakarta, 2021)
The batik group in Jarum village is a group that has had batik skills and play a role in maintaining the existence of Jarum village as a tourist village. But entering the era of the Covid-19 pandemic, the batik group in Jarum village experienced many complex problems related to creativity in the development of batik products and management of branding promotion governance in the Covid-19 pandemic. The urgency of the situation, then through the implementation of the P3WILSEN Program from ISI Yogyakarta is trying to offer alternative programs for developing batik designs and products, as well as the assistance of social media management. In the implementation of art counselling activities, this time using the method of literature studies, discussions, lectures, and experimental methods. The application of this method is intended so that the way obtained in the learning process gets optimal results. The result of the P3WILSEN program is creating a new creation batik motif Mojo Arum that has been registered in Intellectual Property Rights and making promotion branding Nunggak Semi. It is expected that in the future, there will be follow-up with the implementation of other mentoring programs that synergize and be sustainable. Kelompok batik di Desa Jarum merupakan kelompok yang telah memiliki keterampilan membatik dan berperan dalam menjaga eksistensi Desa Jarum sebagai desa wisata. Namun memasuki era pandemi Covid-19, kelompok batik di Desa Jarum banyak mengalami permasalahan yang cukup kompleks, terkait dengan kreativitas dalam pengembangan produk batik dan manajemen tata kelola promosi branding di pandemi Covid-19. Adanya urgensi permasalah tersebut, maka melalui pelaksanaan Program P3wilsen dari ISI Yogyakarta ini mencoba menawarkan alternatif program pengembangan desain dan produk batik, serta pendampingan manajemen media sosial. Dalam pelaksanaan kegiatan penyuluhan seni kali ini digunakan metode kajian literatur, diskusi, ceramah, dan metode eksperimen. Penerapan metode ini dimaksudkan agar cara yang diperoleh dalam proses belajar mendapatkan hasil yang optimal. Hasil capaian Kegiatan P3wilsen, yaitu pembuatan motif batik kreasi baru Mojo Arum yang telah terdaftar dalam Hak Kekayaan Intelektual dan menciptakan branding promosi Nunggak Semi. Diharapkan ke depan terdapat tindak lanjut dengan pelaksanaan program pendampingan lainnya yang saling bersinergi dan berkesinambungan.